Investigating the filament winding process of composites manufacturing (B169) - Sim, Darren Zhiyi (Nanyang Technological University, 2021)
The in-situ consolidation of the commingled yarn during filament winding is demonstrated on both Glass fibre – reinforced polyamide6 and Carbon fibre – reinforced Polyetherimide. Additionally, compress moulding of carbon fibre – reinforced polyetherimide will also be investigated. This study aim was to reduce the void content to less than 5% by optimizing the various parameters. The parameters include the winding speed, temperature of a heat gun and preheater ring, and pressure. The quality of the fabrication will then be assessed by the void content as well as the mechanical strength of the component. The results show that having a pressure of 1.5MPa and a combination of winding speed is important in achieving high flexural modulus in both compress moulding and in-situ consolidation process, respectively. The results will serve as a guideline for manufacturers or future research purposes in selecting the suitable pressure and winding speed.